THE RELATION OF STRESS LEVEL WITH FLUOR ALBUS EVENTS FOR TEENAGE GIRLS ATT SMP TAMAN SISWA MOJOKERTO - veryudha eka prameswari; indra yulianti; Nailatul Magfiroh (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Flour albus is a condition that is often experienced by women. There are many causes that make flour albus it appears one of them is the factor of fatigue and stress Flour albus is not worried the woman if her condition is normal and does not cause odor and different color. Flour albusakibat stress often occurs in adolescents and adult women. Flour albus due to stress will cause problems on the genitalia it is often characterized by conditions itchy, the color of different liquids on genitalia and discomfort in the area of her vital research purposes research purposes know the correlation between stress and the incidence of flour albus in adolescent girls in SMP Taman Siswa Mojokerto PIn this study the types of analytic correlation of population are all teenage girls in Taman Siswa junior Mojokerto 415 students were 83 students in the engineering side Strativiet use random sampling. the independent variable is the level of stress and the incidence of flour albus dependenya is a questionnaire measuring instrument. Data collection, processing and analysis of data Editing, Coding, Scoring, Tabulation and chi square The results of analysis by chi square test with SPSS 16, the error level of 5% and a value of 0.000 Ï, where Ï = 0.000 <0.05 then H0 H1S accepted or rejected it means there is a relationship with the incidence rate of flour albus stress on young girls in junior Parks students MojokertoBased on the research results there is a correlation with the incidence rate of stress flour albus in adolescent girls in Taman Siswa junior Mojokert Based on the results of research in the know that all respondents had experienced flour albus but steress which has particularly suffered is not the same stress level